2010
DOI: 10.1111/j.1747-1346.2009.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

The Story of Good Citizenship: Framing Public Policy in the Context of Duty‐Based versus Engaged Citizenship

Abstract: Recent studies have explored the dimensions of duty‐based versus engaged citizenship. These studies assert that individuals differ on the question of “what is a good citizen” and somehow suggest that “engaged citizens” are more participatory, global, and committed to social justice than their duty‐based counterparts. In this article, we examine, with an innovative survey methodology and merging of citizenship and framing literature, the potential effects of increased engaged citizenship on policy issues. Our q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 24 publications
1
44
0
1
Order By: Relevance
“…Recall that micro-level hypotheses posit that increases in transportation, breach, narrator trust, congruence, and characters are likely to influence audience members to agree with narrative content. Empirical tests support that narrative transportation (Jones, 2014), congruence (for example, McBeth, Lybecker, and Garner, 2010;Shanahan, Jones, and McBeth, 2011;Jones and Song, 2014;Lybecker, McBeth, and Kusko, 2013;Shanahan, Adams, and McBeth, 2013), and characters (Jones, 2010(Jones, , 2013 are effective in persuading individuals' policy preferences.…”
Section: Drawing On the Work Of Pet Co-creator Bryan Jones (2001) Andmentioning
confidence: 88%
“…Recall that micro-level hypotheses posit that increases in transportation, breach, narrator trust, congruence, and characters are likely to influence audience members to agree with narrative content. Empirical tests support that narrative transportation (Jones, 2014), congruence (for example, McBeth, Lybecker, and Garner, 2010;Shanahan, Jones, and McBeth, 2011;Jones and Song, 2014;Lybecker, McBeth, and Kusko, 2013;Shanahan, Adams, and McBeth, 2013), and characters (Jones, 2010(Jones, , 2013 are effective in persuading individuals' policy preferences.…”
Section: Drawing On the Work Of Pet Co-creator Bryan Jones (2001) Andmentioning
confidence: 88%
“…Mcbeth et al (2010), for instance, did find that people whose understanding of citizenship was duty-based responded more to duty-focused appeals, while engagementbased citizens responded more to engagement-focused appeals. Kim (2012) connected Dalton's work with that of Inglehart (1977) and Giddens (1991) and argued that younger people conceptualize politics as life politics.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Examining climate change narratives, Jones (2011) found higher narrative transportation to be associated with higher levels of persuasion. Examining attitudes regarding recycling, McBeth, Lybecker, and Garner () and Lybecker, McBeth, and Kusko () found that individuals' views of citizenship were congruent with different recycling narratives. Examining support for government intervention in childhood obesity, Husman () found higher support for intervention among individuals exposed to ideologically congruent narratives.…”
Section: Narratives In the Policy Change Literaturementioning
confidence: 99%